Profil Sarana Dan Prasarana Pengajaran Pendidikan Jasmani Di Sekolah Dasar Negeri Kec. Tanete Riattang Barat Kabupaten Bone - muliadi muliadi (Universitas Negeri Makassar, 2019)
This study aims to describe the objective conditions of the profile of facilities and infrastructure for teaching physical education in the State Elementary School of Kec. Tanete Riattang Barat, Kab. This research method uses descriptive design. Data collection is done by questionnaire techniques, documentation and observation. The data analysis used is descriptive quantitative. The results of this study are: (a) the playing field is 100%, (b) the Volleyball court is 25%, and (c) the long jump field is 33.33%. Regarding physical education tools: (a) 91.66% have small balls, (b) 33.33% have soccer balls, (c) 16.66% have handballs, (d) 75% have volleyball, (e) 8.33% have basketball, (f) 41.66% have a high jump tool, (g) 16.66% have a mat, (h) 33.33% have a baton, (i) 41.66 % has a net volley, (j) 16.66% has a rope, (k) no one has a balance beam, (l) no one has a single crossbar, and (m) no one has a basketball hoop. While the ratio for the use of physical education tools is: (a) For small balls the ratio that has the most frequency in using the ball for 30 students with five balls is 8.33%, (b) For soccer balls the ratio has the most frequency with one ball is 25%, (c) For hand balls the ratio that has the most frequency with one ball is 16.66%, (d) For volleyball the ratio that has the most frequency with one ball is 75%, and (e ) For basketball the ratio that has the most frequency with one ball is 8.33%.